Recent Process in the Inhibitors of UDP-3-O-(R-3-hydroxyacyl)-Nacetylglucosamine Deacetylase (LpxC) Against Gram-Negative Bacteria - Liu, Fang; Ma, Shutao (Mini Reviews in Medicinal Chemistry, 2018)
Infections caused by pathogenic bacteria are a major health concern throughout the world. There is a great need to develop novel antibacterial agents with new mechanisms of action. Lipopolysaccharides (LPS) are the main component of the outer membrane of Gram-negative bacteria, serving as a permeability barrier, which protects the bacteria from many antibiotics. The UDP-3-O-(R-3- hydroxyacyl)-N-acetylglucosamine deacetylase (LpxC), a Zn2+-dependent enzyme, catalyzes the first irreversible step of the biosynthesis of lipid A, the hydrophobic membrane anchor of LPS being essential for cell viability. Additionally, it shares no sequence or structural homology with any mammalian proteins. Therefore, it may become a novel target for the new drugs against Gram-negative bacteria. Thus, research on LpxC inhibitors as new antibacterial agents has become an attractive field in the development of the novel antibiotic therapy of Gram-negative bacteria. In this review, we will summarize the recent progress in the structure and catalytic mechanism of LpxC and the research and development of LpxC inhibitors.
Keywords: biosynthesis